Labour outcomes and family background: evidence from the EU during the Recession - Avram, Silvia; Canto, Olga (Colchester, 2017)
"Using EU-SILC data for 2005 and 2011, we compare the role of family background on labour outcomes in three EU countries that experienced large swings in unemployment during this period. We use a multidimensional family background indicator that avoids undesirable cohort effects. Our results suggest that family background affects employment prospects and job quality (hourly wages and contract insecurity), and that human capital formation explains a significant part (but not all) of the family background effects. There is significant cross-national variation in the extent to which human capital can explain the effects of family background. Finally, we do not find any evidence that the effect of family background is substantially moderated by the economic cycle in any of our countries."